2007
DOI: 10.1002/jcp.21236
|View full text |Cite
|
Sign up to set email alerts
|

Akt kinase targets association of CBP with SMAD 3 to regulate TGFβ‐induced expression of plasminogen activator inhibitor‐1

Abstract: Transforming growth factor-beta (TGFbeta) controls expression of plasminogen activator inhibitor type 1 (PAI-1), which regulates degradation of extracellular matrix proteins in fibrotic diseases. The TGFbeta receptor-specific Smad 3 has been implicated in the PAI-1 expression. The mechanism by which non-Smad signaling contributes to this process is not known. We studied the cross-talk between Smad 3 and PI 3 kinase/Akt signaling in TGFbeta-induced PAI-1 expression in renal mesangial cells. Inhibition of PI 3 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 85 publications
1
84
0
Order By: Relevance
“…Anti-HA antibody was purchased from Covance, Princeton, NJ. Adenovirus vectors expressing HA-tagged Smad 3 (Ad Smad 3) and FLAG-tagged Smad 7 (Ad Smad 7) have been described previously (9). shRNAs targeting two different regions of deptor (deptor sh1 and deptor sh2), FLAG-deptor, and FLAG-deptor 13X were obtained from Addgene and originally constructed in the laboratory of Dr. David M. Sabatini, Whitehead Institute for Biomedical Research, Boston, MA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-HA antibody was purchased from Covance, Princeton, NJ. Adenovirus vectors expressing HA-tagged Smad 3 (Ad Smad 3) and FLAG-tagged Smad 7 (Ad Smad 7) have been described previously (9). shRNAs targeting two different regions of deptor (deptor sh1 and deptor sh2), FLAG-deptor, and FLAG-deptor 13X were obtained from Addgene and originally constructed in the laboratory of Dr. David M. Sabatini, Whitehead Institute for Biomedical Research, Boston, MA.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorylated Smads dissociate from the type I receptor and the SARA (Smad anchor for receptor activation), a Smad-recruiting protein to the plasma membrane (6). Subsequently, phosphorylated Smad 2 and Smad 3 bind to the co-Smad, Smad 4, and the heterodimer translocates to the nucleus to recruit coactivators or corepressors for target gene regulation (7)(8)(9).…”
mentioning
confidence: 99%
“…In renal mesangial cells, TGF-β-induced PI3 Kinase/Akt signaling enhances Smad-mediated PAI-1 expression by promoting CBP-mediated Smad3 acetylation (Das, Ghosh-Choudhury et al 2008). Matsuzaki reported that Jnk, activated by TGF-β, phosphorylates Smad3 at the linker region (pSmad3L), which increases PAI-1 expression in heptocellular carcinoma (HCC) (Matsuzaki, Murata et al 2007).…”
Section: Pai-1 Regulation By Tgf-βmentioning
confidence: 99%
“…Smad-mediated PAI-1 expression is enhanced by promoting CBP-mediated Smad3 acetylation (Das, Ghosh-Choudhury et al 2008). It will be interest to test whether CBP/P300 has a role in this synergistic regulation.…”
Section: Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation